The Icing On The Cake: How Social Media Constructs A Fourth Personality Layer - Robertson, Kayleigh (New Explorations)

(untitled) (New Explorations Association, 2025)
This article presents a critical literature review of the relationship between social media use and thedevelopment of personality disorder features, particularly among young people. Drawing on psychologicaltheory, psychological study, developmental research, and Marshall McLuhan’s famous probe “The medium isthe message” (McLuhan, 1964, p. 7), this review examines key findings across disciplines while offeringinterpretive insights into emerging behavioral patterns. A large body of data now shows a stark rise inindividuals aged 12-25 experiencing mental health issues, including depression, anxiety, suicidality,hospitalizations, and chronic low self-esteem. While these symptoms have been widely discussed, this paperexplores the deeper structural implications of these outcomes—specifically, how long-term social media usemay be shaping identity and contributing to the emergence of Cluster B personality traits, including borderlineand histrionic features, affecting relationships, real-life problems (finding joy, goal setting for the future,employment), and simply “growing up”. Synthesizing studies on self-image, child development, personalitydisorders, and influencer culture, this review highlights a critical gap in current discourse: not just what ishappening to mental health, but why, and the collateral damages of the ripple effects. This review connectsestablished psychological theories to patterns of online behavior, proposing that the medium itself (socialmedia) may be rewiring the developing brain, contributing to a newly dominant FPL or “fourth personalitylayer”—a digital self that increasingly dictates offline thought, behavior, and sense of identity. This reviewcontributes to a deeper understanding of how social media may not just reflect who we are, but activelyconstruct who we become.